Album of Classical Pieces: transcribed for viola and piano, Vol. III - BACH, J.S. (international Music Co., 1948)
Isi lagu dalam album ini antara lain:1. Sarabande from the English Suite No. 5. (J.S. Bach).2. Courante from the "Pieces pour le Clavecin" (George Frederic Handel).3. Aria from the Opera "Armida" (Jean Baptiste Lully).4. "Les Tendres Plaintes" (Jean Philippe Rameau).5. Andante and Gavotte from the opera "Alceste" (Christoph Willibald Von Gluck).6. Minuet ( Giambattista Martini).7. Andante from the Horn Concerto No. 2, K.417 (W.A. Mozart).8. Adagio from the Sonata "Arpeggione" (Franz Schubert).9. 4 Waltzes (Franz Schubert).